Migration Crisis in the EU and Rethinking of Multiculturalism. The Papers of the “Round Table” Conference of the Lecturers and Students of the Peoples’ Friendship University of Russia - Kazarinova, Dar'ya Borisovna; Teplov, Aleksey Vyacheslavovich; Ladygin, Mikhail Sergeevich; Yagodka, Nikolay Nikolaevich (Vestnik Rossijskogo universiteta družby narodov. Seriâ Politologiâ (Online), 2016)
The paper dedicated to the “round-table” conference “Migration crisis in the EU and rethinking of multiculturalism: the European question and the German answer” which was organized by the Department of comparative politics of the Peoples` Friendship University of Russia (PFUR) and held on October 9 2015 on the faculty of the humanities and social sciences. Among the participants of the conference were the lecturers and the students of the PFUR.